Hop 'til you drop - Griffin, J. M. (Griffin, J. M. Jules & Bun mystery., 2021)
In the third installment of J.M. Griffin's series starring rabbit rescue owner Jules Bridge and her telepathic rabbit Bun, when an Easter egg hunt becomes a crime scene, it's up to the pair to crack the case ...